Boundary Conditions: Crossing Spatial Boundaries as a Matter of Mind - van der Elst, Judith (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2018)
A key step in understanding different ways of experiencing the world, consists in exploring the limits of the human mind and the languages we use to make sense of our surrounding worlds. The concept of boundary is central in this endeavor. When we think of a boundary in the broadest sense, we think of an entity (or event) demarcated from its surroundings. Whether these boundaries reflect the structure of the world or just the organizing activity of our mind is a matter of intense philosophical debate. In this paper, human spatial thinking is a starting point to further explore our interactions with and within our environment. I argue that biosemiotics offers the most suitable framework for doing so, as it integrates humans in the larger communication network flow. Yet the spatial aspect of communication has received only limited attention in the biosemiotic literature. Furthermore, basing myself on my recent crossover practice in art/science, I argue that an embodied-embedded approach is necessary to dissolve and redefine spatial categories, allowing the investigation and potential crossing of the boundaries of our perceptual worlds.